Pricing double-barrier options under a flexible jump diffusion model - Cai, Ning; Chen, Nan; Wan, Xiangwei (Operations research letters, 2009)
In this paper we present a Laplace transform-based analytical solution for pricing double-barrier options under a flexible hyper-exponential jump diffusion model (HEM). The major theoretical contribution is that we prove non-singularity of a related high-dimensional matrix, which guarantees the existence and uniqueness of the solution.